Velocity space resolved absolute measurement of fast ion losses induced by a tearing mode in the ASDEX Upgrade tokamak. (15th January 2018) - Galdon-Quiroga, J.; Garcia-Munoz, M.; Sanchis-Sanchez, L.; Mantsinen, M.; Fietz, S.; Igochine, V.; Maraschek, M.; Rodriguez-Ramos, M.; Sieglin, B.; Snicker, A.; Tardini, G.; Vezinet, D.; et al.
Abstract: Absolute flux of fast ion losses induced by tearing modes have been measured by means of fast ion loss detectors (FILD) for the first time in RF heated plasmas in the ASDEX Upgrade tokamak. Up to 30 MW m −2 of fast ion losses are measured by FILD at 5 cm from the separatrix, consistent with infra-red camera measurements, with energies in the range of 250–500 keV and pitch angles corresponding to large trapped orbits. A resonant interaction between the fast ions in the high energy tail of the ICRF distribution and a m / n   =  5/4 tearing mode leads to enhanced fast ion losses. Around 9.3 ± 0.7 % of the fast ion losses are found to be coherent with the mode and scale linearly with its amplitude, indicating the convective nature of the transport mechanism. Simulations have been carried out to estimate the contribution of the prompt losses. A good agreement is found between the simulated and the measured velocity space of the losses. The velocity space resonances that may be responsible for the enhanced fast ion losses are identified.